Integrative Metabolome and Transcriptome Analysis of Flavonoid Biosynthesis Genes in Broussonetia papyrifera Leaves From the Perspective of Sex Differentiation - Jiao, Peng; Chaoyang, Li; Wenhan, Zhai; Jingyi, Dai; Yunlin, Zhao; Zhenggang, Xu (Frontiers in Plant Science, 2022)
Flavonoids are important secondary metabolites involved in plant development and environmental responses. Sex differences in flavonoids are common in plants. Broussonetia papyrifera is a dioecious plant that is rich in flavonoids. However, few studies have been done on its molecular mechanism, especially sex differences. In the present study, we performed an integrated transcriptomics and metabolomics analysis of the sex differences in the accumulation of flavonoids in B. papyrifera leaves at different developmental stages. In general, flavonoids accumulated gradually with developmental time, and the content in female plants was higher than that in male plants. The composition of flavonoids in female and male plants was similar, and 16 kinds of flavonoids accumulated after flowering. Correspondingly, a significant enrichment of differentially expressed genes and metabolites was observed in the flavonoid biosynthesis pathway. WGCNA and qRT-PCR analyses identified several key genes regulating the accumulation of flavonoids, such as those encoding CHS, CHI and DFR. In addition, 8 TFs were found to regulate flavonoid biosynthesis by promoting the expression of multiple structural genes. These findings provide insight into flavonoid biosynthesis in B. papyrifera associated molecular regulation.